2015
DOI: 10.1021/ef501847q
|View full text |Cite
|
Sign up to set email alerts
|

Role of Physicochemical and Interfacial Properties on the Binary Coalescence of Crude Oil Drops in Synthetic Produced Water

Abstract: An important aspect of efficient treatment of produced water is to promote the coalescence of dispersed oil drops. Therefore, a fundamental understanding of the relations between interfacial and physicochemical properties of crude oils and the coalescence process is essential, and elucidating these relationships was the aim of this investigation. Nine crude oils and fractions of two crude oils, where acids, bases, and asphaltenes were selectively extracted, were included in the studies. The dynamic interfacial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…The higher water-in-oil emulsion stability for the systems with the lighter crude oils was explained by the high saturate and low aromatic contents in these oils. This can facilitate increased interfacial activity, as well as the aggregation of asphaltenes, resulting in rigid interfacial layers that enhanced the emulsion stability 19,38,40 . It was also argued by other authors that wax particles, often found in light crude oils, can increase the emulsion stability 41 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher water-in-oil emulsion stability for the systems with the lighter crude oils was explained by the high saturate and low aromatic contents in these oils. This can facilitate increased interfacial activity, as well as the aggregation of asphaltenes, resulting in rigid interfacial layers that enhanced the emulsion stability 19,38,40 . It was also argued by other authors that wax particles, often found in light crude oils, can increase the emulsion stability 41 .…”
Section: Resultsmentioning
confidence: 99%
“…The interfacial activity of components in the crude oils will be affected by these parameters and can lead to increased emulsion stability and problems with separation [17][18] . It has been shown that the interfacial properties can influence the coalescence of oil droplets 19 and the stability of oilin-water emulsions [20][21] . Once in contact with an aqueous phase, water-soluble hydrocarbons in the crude oil will partition into the water phase [22][23][24] , adsorb at the gas-water interfaces and influence the oil removal efficiency by gas flotation [25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of the coalescence of model oil-in-water drops had been conducted [7][8][9] . Regarding the crude oil systems, the researchers have paid more attention to the coalescence of water drops in the continuous oil phase [10][11][12][13] , leaving the crude oil-in-water systems a relatively unexplored topic [14][15] . In addition, there are hardly any research tools that allow systematically investigating the coalescence of crude oil drops in water.…”
Section: Figure 1 Typical Produced Water Treatment Processmentioning
confidence: 99%
“…Drainage and coalescence time are often used interchangeably, even though some authors divide the coalescence time into drainage and rupture times 8 . In dynamic conditions, however, the value of the rupture time is orders of magnitude lower and the difference between the drainage and coalescence time becomes negligible.…”
Section: Introductionmentioning
confidence: 99%